Developing and implementing national health identifiers in resource limited countries: why, what, who, when and how?. Issue 1 (1st January 2018) - Beck, Eduard J.; Shields, J. Mark; Tanna, Gaurang; Henning, Gerrit; de Vega, Ian; Andrews, Gail; Boucher, Philippe; Benting, Lionel; Garcia-Calleja, Jesus Maria; Cutler, John; Ewing, Whitney; Kijsanayotin, Boonchai; et al.
ABSTRACT: Many resource-limited countries are scaling up health services and health-information systems (HISs). The HIV Cascade framework aims to link treatment services and programs to improve outcomes and impact. It has been adapted to HIV prevention services, other infectious and non-communicable diseases, and programs for specific populations. Where successful, it links the use of health services by individuals across different disease categories, time and space. This allows for the development of longitudinal health records for individuals and de-identified individual level information is used to monitor and evaluate the use, cost, outcome and impact of health services. Contemporary digital technology enables countries to develop and implement integrated HIS to support person centred services, a major aim of the Sustainable Development Goals . The key to link the diverse sources of information together is a national health identifier (NHID). In a country with robust civil protections, this should be given at birth, be unique to the individual, linked to vital registration services and recorded every time that an individual uses health services anywhere in the country: it is more than just a number as it is part of a wider system. Many countries would benefit from practical guidance on developing and implementing NHIDs. Organizations such as ASTM and ISO, describe the technical requirements for the NHID system, but few countries have received little practical guidance. A WHO/UNAIDS stake-holders workshop was held in Geneva, Switzerland in July 2016, to provide a 'road map' for countries and included policy-makers, information and healthcare professionals, and members of civil society. As part of any NHID system, countries need to strengthen and secure the protection of personal health information. While often the technology is available, the solution is not just technical. It requires political will and collaboration among all stakeholders to be successful.